2021
DOI: 10.3390/biomedicines9081027
|View full text |Cite
|
Sign up to set email alerts
|

How Are Adenosine and Adenosine A2A Receptors Involved in the Pathophysiology of Amyotrophic Lateral Sclerosis?

Abstract: Adenosine is extensively distributed in the central and peripheral nervous systems, where it plays a key role as a neuromodulator. It has long been implicated in the pathogenesis of progressive neurogenerative disorders such as Parkinson’s disease, and there is now growing interest in its role in amyotrophic lateral sclerosis (ALS). The motor neurons affected in ALS are responsive to adenosine receptor function, and there is accumulating evidence for beneficial effects of adenosine A2A receptor antagonism. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 179 publications
(296 reference statements)
0
1
0
Order By: Relevance
“…Mori et al concluded that adenosine's action at A2ARs has been found to play a role in the pathophysiology and development of ALS. However, future studies are still needed to prove that claim [ 21 ]. The review's shortcoming was that it highlighted many adenosine properties without emphasizing UA and not stressing which studies have shown it to be the critical component in neuroprotective effects as it is the end product of adenosine.…”
Section: Reviewmentioning
confidence: 99%
“…Mori et al concluded that adenosine's action at A2ARs has been found to play a role in the pathophysiology and development of ALS. However, future studies are still needed to prove that claim [ 21 ]. The review's shortcoming was that it highlighted many adenosine properties without emphasizing UA and not stressing which studies have shown it to be the critical component in neuroprotective effects as it is the end product of adenosine.…”
Section: Reviewmentioning
confidence: 99%
“…A study from Vincenzi et al reported an upregulation of A 2A AR receptors in the lymphocytes of people affected byALS [31], while Yoshida et al measured adenosine levels in the cerebrospinal fluid of ALS patients, finding out that these were significantly higher withrespect to the control subjects [32]. Unexpectedly, treatment with the A 2A AR antagonist caffeine (Figure 2, panel A), which is usually referred to as a protective agent against Alzheimer's Disease (AD) and Parkinson's Disease (PD), was demonstrated to shorten the survival of ALSaffected SOD1 G93A mice, a well-known experimental model for ALS (Potenza et al) [33], even if some explanation for this phenomenon can be provided bythe non-selectivity of caffeine [34]. Indeed, Ng et al showed that suppression of A 2A AR signaling delays the progression of ALS in the same SOD1 G93A mouse model [35].…”
Section: Gpcrs Involved In Alsmentioning
confidence: 99%
“…mental model for ALS (Potenza et al) [33], even if some explanation for this phenomenon can be provided bythe non-selectivity of caffeine [34]. Indeed, Ng et al showed that suppression of A2AAR signaling delays the progression of ALS in the same SOD1 G93A mouse model [35].…”
Section: Gpcrs Involved In Alsmentioning
confidence: 99%
“…Adenosine receptors are widely expressed throughout the central nervous system and peripheral tissues or cells (for recent reviews, see Chen, 2014 [ 7 ]; Mori 2021 [ 10 ]) [ 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. They belong to the family of G protein-coupled receptors (GPCRs), which possess seven transmembrane alpha helices, with three intracellular loops and three extracellular loops [ 11 , 21 ].…”
Section: Introductionmentioning
confidence: 99%